2009
DOI: 10.1192/bjp.bp.108.056531
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of a parenting intervention for children at risk of developing conduct disorder

Abstract: Early parent-based intervention reduced child antisocial behaviour and benefits were maintained, with reduced reliance on health and social service provision, over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 28 publications
4
102
2
1
Order By: Relevance
“…Two studies of IY with longer-term follow-ups found that improvements in ECBI-I score were sustained and accompanied by decreased costs of health and social services or a reduction in the likelihood that formal services were used. 172,173 The US-based evaluation of the multifaceted Perry Preschool Program suggests a possible long-term impact on conduct disorder, criminal behaviour and employment. 174 Evidence from model-based analyses suggests that parenting programmes are likely to provide substantial savings (e.g.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…Two studies of IY with longer-term follow-ups found that improvements in ECBI-I score were sustained and accompanied by decreased costs of health and social services or a reduction in the likelihood that formal services were used. 172,173 The US-based evaluation of the multifaceted Perry Preschool Program suggests a possible long-term impact on conduct disorder, criminal behaviour and employment. 174 Evidence from model-based analyses suggests that parenting programmes are likely to provide substantial savings (e.g.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…By contrast, the control group received a less intensive programme but exhibited no evidence of long-run gains. Furthermore, Bywater et al [30] show that significant improvements in primary measures of child behaviour resulting from an evaluation of the IY parenting programme conducted in Wales were maintained in the medium term (18 months after baseline). In addition, Webster-Stratton, Rinaldi and Reid carried out assessments of participants 8-12 years after contact with the programme [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interventions focused on changing parenting style can offer an effective and economically efficient way of identifying and managing the risks associated with childhood conduct problems [23,24]. Research supports the efficacy of such programmes in reducing the intensity of conduct problems, both in the short term [25][26][27][28] and in the longer term [15,29,30]. A systematic overview of the economic evidence on the effectiveness of parenting programmes is given by Charles et al [31].…”
Section: Introductionmentioning
confidence: 99%
“…These interventions were shown to be clearly cost-effective (Bywater et al, 2009;Jones et al, 2008). Scott (2007) commented, on the basis of this and earlier research, including Scott et al (2001), that although these interventions were relatively expensive (about ÂŁ1,800 per family), in the long run these interventions could be very cost effective, given the known costs of children who enter cycles of juvenile delinquency and rebellion in school and community.…”
Section: Sure Start's Developing Successmentioning
confidence: 89%